Phenotypic and molecular characterization of Salmonella enterica isolated from retail beef in Peshawar, Pakistan - Muhammad Jawad Ullah; Kafeel Ahmad; Fawad Inayat; Faryal Khattak; Sawaira Huriya; Fai Sal (PLoS ONE, 2026)
Salmonella enterica is a major foodborne pathogen associated with beef contamination and increasing antimicrobial resistance, particularly in low- and middle-income countries. This study investigated the prevalence, antimicrobial resistance patterns, and genetic diversity of S. enterica isolated from retail beef samples in Peshawar, Pakistan, using combined phenotypic and molecular approaches. A total of 250 beef samples were collected from urban, rural, and peri-urban retail markets. Salmonella enterica was isolated using standard culture and biochemical methods and confirmed by PCR targeting the invA gene. Antimicrobial susceptibility was determined by the Kirby–Bauer disk diffusion method, and genetic diversity was assessed using randomly amplified polymorphic DNA PCR (RAPD-PCR). Overall, S. enterica was detected in 150 samples (60.0%), with higher prevalence in rural markets (77.5%) compared with urban (52.5%) and peri-urban (50.0%) locations. A high percentage of isolates were resistant to azithromycin (94.0%), tetracycline (68.7%), and streptomycin (52.0%), indicating widespread multidrug resistance among isolates. Five isolates (3.3%) were identified as extended-spectrum β-lactamase (ESBL) producers and carried bla TEM-1, bla CTX-M-15, or bla SHV-12 genes. RAPD-PCR analysis revealed substantial genetic heterogeneity, with isolates distributed across multiple phylogenetic clusters, suggesting diverse contamination sources rather than clonal dissemination. These findings indicate that retail beef in Peshawar represents a significant reservoir of genetically diverse and antimicrobial-resistant S. enterica . The combined use of phenotypic methods with targeted molecular and low-cost genotyping approaches provides a practical framework for surveillance of foodborne Salmonella in resource-limited settings.